Development of Powtoon-Assisted Animation Video for Poetry Writing Material in Grade VIII at SMPN 1 Sitiung - Salahuddin, Amar; Marlianda, Rendi; Yani, Rahma (The Future of Education Journal, 2025)
This study aims to develop a learning media using Powtoon-assisted animation videos for teaching poetry writing. The researcher chose the CapCut application because it is accessible and easy to use for creating learning videos that actively engage students' visual and auditory senses, enhancing the absorption of the material. This research employed a Research and Development (R&D) method using the 4D model, which consists of the stages: define, design, develop, and disseminate. The study was conducted at SMPN 1 Sitiung in the 2025/2026 academic year, with 29 grade VIII students as participants. Data collection techniques included questionnaires for student responses, teacher responses, media expert validation sheets, material expert validation sheets, and language expert validation sheets. The results show that the researcher successfully developed a learning video as a teaching aid for reading poetry texts. The video was considered valid based on expert validations: media expert validation scored 100%, categorized as "very valid," material expert validation scored 70%, categorized as "valid," and language expert validation scored 97.1%, categorized as "very valid." This indicates that the learning video is suitable for use by both teachers and students. The practicality assessment, conducted by the teacher, scored 96.3%, categorized as "very valid," and the grade VIII students scored 97.6%, also categorized as "very valid." Therefore, it can be concluded that the developed learning video is eligible for use, as it meets the criteria of validity, practicality, and effectiveness.